Copper(ii) mediated phenol ring nitration by nitrogen dioxide. Issue 46 (30th October 2015) - Kumar, Vikash; Ghosh, Somnath; Saini, Anoop Kumar; Mobin, Shaikh M.; Mondal, Biplab
Abstract : Addition of nitrogen dioxide in the THF solutions of Cu(ii ) complexes of N2 O2 type ligands, L 1 H2 and L 2 H2 resulted in the nitration at the 4-position of coordinated equatorial phenolate ring of the ligand frameworks. Spectroscopic evidence suggests that the reaction proceeds through a phenoxyl radical complex formation. Abstract : Cu(ii ) complexes of N2 O2 type ligands, L 1 H2 and L 2 H2 [L 1 H2 = 6, 6′-(((pyridin-2-ylmethyl)azanediyl)bis(methylene))bis(2, 4-di- tert -butylphenol); L 2 H2 = 2, 4-di- tert -butyl-6-(((3-( tert -butyl)-2-hydroxy-5-methylbenzyl)(pyridin-2-yl-methyl)amino)methyl)phenol], have been synthesized. Addition of nitrogen dioxide (NO2 ) in THF solutions of the complexes resulted in the nitration at the 4-position of a coordinated equatorial phenolate ring of the ligand frameworks. This nitration did not occur at the phenol ring which is axially coordinated to the metal center. Spectroscopic evidence suggests that the reaction proceeds through a phenoxyl radical complex formation.